Drug Repurposing: An Overview - Saini, Mahendra; Parihar, Nikhita; Soni, Shankar Lal; Sharma, Vandana (Asian Journal of Pharmaceutical Research and Development, 2020)
Drug repurposing (also known as drug repositioning) means finding novel indications for currently marketed drugs. This strategy may reduce the costs of new drug development and advance the delivery of new therapeutics to patients with incurable diseases. By specifically regulating multiple targets, more effective drugs can be developed through polypharmacology. Drug repositioning is underpinned by the fact that common molecular pathways contribute to many different diseases. Various data-driven and experimental approaches have been suggested for the identification of repurposable drug candidates; however, there are also major technological and regulatory challenges that need to be addressed. In this Review, we present approaches used for drug repurposing, discuss the challenges faced by the repurposing community and recommend innovative ways by which these challenges could be addressed to help realize the full potential of drug repurposing.